Investing in democracy engaging citizens in collaborative governance - Sirianni, Carmen (Brookings Institution Press, 2009)
"Discusses how government can serve as a partner and catalyst for collaborative problem solving. Details three success stories and explains what measures were taken and why they succeeded. Distills eight core design principles that characterize effective collaborative governance and concludes with concrete recommendations for federal policy"--Provided by publisher.